Android mobile application for a web-based digital asset management system - Han, Yu Huan (2019)
Cognitive skills development has been playing a big role in establishing learning skills. Several applications have been created to help in the development of cognitive skills. Many of the applications have successfully helped children in improving their cognitive skills. Smart Brain Trainer (SBT) application is an education game that trains children on their cognitive skills to improve reaction time and inspection time. With technology advancement, mobile devices have become significantly popular, thus a mobile version of the application is considered as a must to extend the current web-based application effectively and to extend user experience by enjoying the game even outdoor. This project aims to develop a stable and user-friendly Android game application with reference to the SBT web application. In this project, SBT Android application will train children on their cognitive skills, mainly on improving their reaction time and inspection time. There is a total of 4 mini games in SBT Android application with many different game modes for each mini game. All mini games included in SBT Android uses speech activity recognition instead of the usual. With the mini games, user testing was done and the effectiveness of SBT Android application for different age groups were identified. As the result of this project, SBT Android application has been created with similar interfaces, which improve children reaction time and inspection time based on the 4 mini games available.